Impact of Bankruptcy on Rivals: How Tech Overlap and Diversification Affects Value Redistribution - Arthurs,Jonathan; Cho,Sam Yul; Choi,Yohan; Hemmatian,Iman; Joshi,Amol (Academy of Management Proceedings, 2017)
Prior research on bankruptcy proposes two potential outcomes for a bankrupt firm’s industry rivals: a contagion effect wherein rivals’ stock prices decline, and a competitive effect wherein rivals benefit from a competitor’s decline. Although empirical evidence substantiates the contagion effect, existing studies do not consistently account for the competitive effect. We develop and test theory explaining how the degree of technology overlap and diversification strategy of competitors influences the severity of the contagion effect and the expected occurrence of the competitive effect among rivals. We find that greater technology overlap among a bankrupt firm and its competitors exacerbates the contagion effect. Furthermore, competitors with higher unrelated diversification are more susceptible to contagion, while competitors with higher related diversification benefit more from a rival’s bankruptcy.
Keywords: Strategy & Entrepreneurship